The KfW/ZEW start-up panel: design and research potential - Helmut Fryges; Sandra Gottschalk; Karsten Kohn (Institute for the Study of Labor (IZA), 2009)
So far, there has been no data set which observes firm formations in Germany not only on a cross-sectional basis using one-time surveys, but continuously over a number of years. Therefore, the Centre for European Economic Research (ZEW), KfW Bankengruppe and Creditreform set up a panel study of newly founded firms in Germany: the KfW/ZEW Start-up Panel. In each of the yearly panel waves computer-aided telephone interviews (CATI) are conducted with about 6,000 start-up firms from almost all industries. The KfW/ZEW Start-up Panel will for the first time enable profound analyses of the temporal development of newly founded firms, including studies of firm survival. This paper describes the design of the KfW/ZEW Start-up Panel. The survey's research potential is illustrated using data from the first panel wave conducted in the year 2008. Data access for external researchers and data protection issues of the confidential micro data are discussed.
Keywords: C80; L20; J20; G30; 330; Firm foundation; micro data; firm data; panel data; Germany; Unternehmensgründung; Panel; Mikrodaten; Unternehmensentwicklung; Datenschutz; Deutschland